Effect of slug grazing on biomass production of a plant community during a short-term biodiversity experiment - Lanta, Vojtěch (Acta oecologica (Montrouge), 2007)
While recent theoretical work has demonstrated several mechanisms whereby more diverse communities can exhibit greater resistance against herbivore pressure, empirical examinations have been few and the subject of much debate. The aim of this microcosm experiment was to determine how selectivity of grazing by herbivores affected relationships between plant species number and productivity within artificially created grassland communities. The influence of the slug, Arion lusitanicus, was assessed at four levels of plant species diversity (one, two, four and six species per aquarium). The proportion of biomass of particular species eaten by a slug was estimated on the basis of comparison of paired plots. The biomass in control (ungrazed) plots was compared with the biomass in grazed plots. A significant interaction between the number of plant species and slug grazing for aboveground biomass was found, indicating a gradual decrease in the effect of grazing pressure with increased species richness. Positive average values of the complementarity effect and overyielding index, and negative values of the selection effect, indicated niche resource partitioning between species in grazed plots. The electivity index of food selectivity suggested that food selectivity was more pronounced under higher plant species diversity.